Effect of Calcination and Reduction Temperatures on the Catalytic Activity of Ru/La0.5Ce0.5O1.75 for Ammonia Synthesis under Mild Conditions. Issue 6 (22nd April 2020) - Ogura, Yuta; Asai, Takahiro; Sato, Katsutoshi; Miyahara, Shin-ichiro; Toriyama, Takaaki; Yamamoto, Tomokazu; Matsumura, Syo; Nagaoka, Katsutoshi
Abstract : Ammonia is a potential carrier of hydrogen as a zero‐emission fuel. Herein, the effects of calcination and reduction temperatures on the ammonia‐synthesis activity of Ru/La0.5 Ce0.5 O1.75 are investigated under mild synthesis conditions (≤400 °C, ≤3 MPa), which are the preferred conditions for the storage of hydrogen as an energy source. The highest catalytic activity is obtained after calcination of the support at 700 °C and reduction of the catalyst at 650 °C. Calcination using a higher temperature than that used for reduction results in the induction of a strong metal–support interaction (SMSI) effect. This high‐temperature calcination also provides heat resistance to the support, which prevents sintering of the primary support particles during reduction. Thus, calcination and reduction at temperatures higher than those normally used for the preparation of Ru catalysts provide a novel approach for obtaining supported highly dispersed Ru catalysts exhibiting the SMSI effect and high catalytic activities. Abstract : The effect of high‐temperature calcination of the La0.5 Ce0.5 O1.75 support is examined. Calcination at high temperature prevents sintering of the support and agglomeration of Ru particles during reduction of Ru/La0.5 Ce0.5 O1.75 catalyst at high temperature. The obtained catalysts are electron rich, have a high number of active sites, and have high NH3 ‐synthesis activity.